Sulfur‐Based Catholyte Solution with a Glass‐Ceramic Membrane for Li–S Batteries. Issue 1 (28th October 2015) - Wang, Lina; Zhao, Yu; Thomas, Morgan L.; Dutta, Arghya; Byon, Hye Ryung
Abstract: Shuttling of soluble polysulfide species within electrodes is one of the most challenging issues in lithium–sulfur (Li–S) batteries. The resulting deposition of polysulfide species reduces the conductivity of the metallic Li electrode and the quantity of active material. Here, we demonstrate pronounced suppression of polysulfide shuttle using a sulfide‐impermeable glass‐ceramic membrane, which is employed as separator between the positive and negative electrodes. As a result, highly stable Li–S electrochemistry occurs in the sulfur‐dissolving tetrahydrofuran catholyte solution, which provides good capacity retention and Coulombic efficiency for cycling. This demonstration holds promise for practical next‐generation batteries with marked reversibility and the possibility to increase the energy density when equipped with a catholyte flow‐through mode. Abstract : Shuttle suppression : A parasitic internal‐shuttle effect associated with intermediates of lithium polysulfides is prevented in a catholyte‐based lithium–sulfur (Li–S) battery using a glass‐ceramic membrane. The highly reversible Li–S electrochemistry provides great capacity retention and Coulombic efficiency.